Medical students’ awareness of radiation exposure related to radiological imaging procedures - Jończyk-Potoczna, Katarzyna; Strzelczuk-Judka, Lidia; Szłyk, Ewa; Stefaniak, Łucja (Journal of Medical Science, 2014)
Introduction. Current advancements in fields of medical sciences resulted in an increase of imaging examinations with a use of ionising radiation. Such increase leads to justified concerns about its possible consequences.Aim. Assessment of awareness and level of knowledge of medicine students in terms of ionising radiationMaterial and methods. Statistical analysis of 207 surveys of medical students from University of Medical Sciences in Poznan (UMP), Poland with use of Statistica softwareResults. There was no significant difference between the results of the assessment related to gender, year of studies or attendance to radiology classes. Conclusions. Students level of knowledge about the ionising radiation was unsatisfactory. A change in training program can be a benefit for patients and physicians.
Keywords: medical students; ionising radiation; radiological protection